Functional Similarity between the Peroxisomal PTS2 Receptor Binding Protein Pex18p and the N-Terminal Half of the PTS1 Receptor Pex5p - Schäfer, Antje (American Society for Microbiology, 2004)
Within the extended receptor cycle of peroxisomal matrix import, the function of the import receptor Pex5p comprises cargo recognition and transport. While the C-terminal half (Pex5p-C) is responsible for PTS1 binding, the contribution of the N-terminal half of Pex5p (Pex5p-N) to the receptor cycle has been less clear. Here we demonstrate, using different techniques, that in Saccharomyces cerevisiae Pex5p-N alone facilitates the import of the major matrix protein Fox1p. This finding suggests that Pex5p-N is sufficient for receptor docking and cargo transport into peroxisomes. Moreover, we found that Pex5p-N can be functionally replaced by Pex18p, one of two auxiliary proteins of the PTS2 import pathway. A chimeric protein consisting of Pex18p (without its Pex7p binding site) fused to Pex5p-C is able to partially restore PTS1 protein import in a PEX5 deletion strain. On the basis of these results, we propose that the auxiliary proteins of the PTS2 import pathway fulfill roles similar to those of the N-terminal half of Pex5p in the PTS1 import pathway.